Safety profile of magnetic sphincter augmentation for gastroesophageal reflux disease - Froiio, Caterina; Aiolfi, Alberto; Bona, Davide; Bonavina, Luigi (Frontiers in Surgery, 2023)
Background. The magnetic sphincter augmentation (MSA) procedure is an effective treatment for gastroesophageal reflux disease (GERD). Adverse events requiring MSA device removal are rare, but the true prevalence and incidence may be underestimated.Retrospective study on a prospectively collected database. Patients who underwent MSA procedure between March 2007 and September 2021 in two tertiary-care referral centers for esophageal surgery were included. The trend of MSA explant, the changes in the sizing technique and crura repair over the years, the technique of explant, and the clinical outcomes of the revisional procedure were reviewed.Results. Out of 397 consecutive patients, 50 (12.4%) underwent MSA removal, with a median time to explant of 39.5 [IQR=53.7] months. Main symptoms leading to removal were dysphagia (43.2%), heartburn (25%), and epigastric pain (13.6%). Erosion occurred in 2.5% of patients. Smaller (12-and 13-bead) devices were the ones most frequently explanted. The majority of the explants were performed laparoscopically with endoscopic assistance. There was no perioperative morbidity, and the median length of stay was 2.8+1.4 days. After 2014, changes in sizing technique and crura repair resulted in a decreased incidence of explants from 23% to 5 % (p<0.0001). Multivariate analysis confirmed the protective role of added bead units [HR 0.06 (95%CI=0.001-0.220); p<0.000].Oversizing and full mediastinal dissection with posterior hiatoplasty may improve the outcomes of the MSA procedure and possibly reduce removal rates.